The perception of medical residents and faculty members on resident duty hour regulation - Han, Eui-Ryoung; Chung, Eun-Kyung (Korean journal of medical education, 2020)
This study investigated the perceptions of medical residents and faculty members before the implementation of the duty hour regulation in December 2017. A survey was administered to 263 residents and 358 faculty members in the Chonnam National University Hospital. The subjects were given a self-administered structured questionnaire designed to measure their perspectives on duty hour regulation. They were also asked to answer an open-ended question regarding their expectations or concerns regarding duty hour regulation. The response rates were 50.2% for residents and 24.0% for faculty members. Residents and faculty members regarded the improvement of junior residents' well-being favorably, but had conflicting views regarding senior residents. Residents expressed difficulty in completing unchanged workloads within the limited time, while faculty members were more concerned about worsening patient safety due to the discontinuity of care and insufficient resident education. Medical residents and faculty members had differing concerns regarding duty hour regulation. Further studies and the development of future policies should be considered to improve resident education and patient safety within the limited duty hour regulation.